Evaluation of the European Union’s Policy of Cryptocurrencies‘ Regulation - Turskytė, Ieva; Šapkauskienė, Alfreda (Buhalterinės apskaitos teorija ir praktika, 2021)
In 2008, a global financial crisis happened. It led to strong currency price volatility. Because of that, discussions on the need for an alternative, institution-independent currency occurred. Due to this reason the first decentralized cryptocurrency Bitcoin was created. The new and not yet explored concept of cryptocurrency changed the previously strictly defined role of money. Currently, with the growth of the cryptocurrency market, the most important regional institutions (e.g. FED, EBA) provide regulatory guidelines of a recommendatory nature. The regulations of these institutions remain significant, reflecting the dominant approach to digital money. Because of this reason, the aim of the study is to identify the factors that determine the difficulties in the legalization process of cryptocurrencies and to investigate the features of the European Union's cryptocurrency regulatory policy. Methods used: analysis of scientific literature and legal documents, systematization, comparison, interpretation and generalization of information. The results of the study show that the European Union has taken active regulatory action with the growing importance of cryptocurrencies in the world. To date, a document regulating the definition of cryptocurrencies has not yet been adopted at Union level, but the adoption of the cryptocurrency regulation proposal presented in 2020 would mean greater clarity and security for cryptocurrency issuers, intermediaries and users.
Keywords: cryptocurrency; European Union; regulation